Childhood trauma and treatment outcome in bipolar disorder. Issue 4 (7th August 2016) - Cakir, Sibel; Tasdelen Durak, Rumeysa; Ozyildirim, Ilker; Ince, Ezgi; Sar, Vedat
ABSTRACT: The aim of the present study was to investigate the potential influence of childhood trauma on clinical presentation, psychiatric comorbidity, and long-term treatment outcome of bipolar disorder. A total of 135 consecutive patients with bipolar disorder type I were recruited from an ongoing prospective follow-up project. The Childhood Trauma Questionnaire and the Structured Clinical Interview for DSM–IV Axis I Disorders were administered to all participants. Response to long-term treatment was determined from the records of life charts of the prospective follow-up project. There were no significant differences in childhood trauma scores between groups with good and poor responses to long-term lithium treatment. Poor responders to long-term anticonvulsant treatment, however, had elevated emotional and physical abuse scores. Lifetime diagnosis of posttraumatic stress disorder (PTSD) was associated with poor response to lithium treatment and antidepressant use but not with response to treatment with anticonvulsants. Total childhood trauma scores were related to the total number of lifetime comorbid psychiatric disorders, antidepressant use, and the presence of psychotic features. There were significant correlations between all types of childhood abuse and the total number of lifetime comorbid psychiatric diagnoses. Whereas physical neglect was related to the mean severity of the mood episodes and psychotic features, emotional neglect was related to suicide attempts. A history of childhood trauma or PTSD may be a poor prognostic factor in the long-term treatment of bipolar disorder. Whereas abusive experiences in childhood seem to lead to nosological fragmentation (comorbidity), childhood neglect tends to contribute to the severity of the mood episodes.